2019
DOI: 10.1103/physrevc.100.035206
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon resonances with hidden charm in γp reactions

Abstract: PACS numbers: 25.20. Lj, 24.85.+p Typeset by REVT E X

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 112 publications
0
43
0
Order By: Relevance
“…Indeed, the underlying physics of the AFCI discussed here is general and model independent. In the SM, we show the emergence of AFCI and QAHE in a two-orbital Hubbard model [31][32][33] realizable in cold atoms on optical lattices [34,35] where both the sublattice potential and SOI can be tuned optically [36][37][38]. Possible hosting 2D materials for the AFCI include the honeycomb lattice, noncentrosymmetric NiRuCl 6 with strong SOI [39] and the deposition of heavy atoms with strong SOI on insulating magnetic substrates such as MnTe [40] proposed recently by DFT calculations.…”
Section: Pacs Numbersmentioning
confidence: 94%
“…Indeed, the underlying physics of the AFCI discussed here is general and model independent. In the SM, we show the emergence of AFCI and QAHE in a two-orbital Hubbard model [31][32][33] realizable in cold atoms on optical lattices [34,35] where both the sublattice potential and SOI can be tuned optically [36][37][38]. Possible hosting 2D materials for the AFCI include the honeycomb lattice, noncentrosymmetric NiRuCl 6 with strong SOI [39] and the deposition of heavy atoms with strong SOI on insulating magnetic substrates such as MnTe [40] proposed recently by DFT calculations.…”
Section: Pacs Numbersmentioning
confidence: 94%
“…Using an effective Lagrangian approach, the photoproduction of these P c states is also investigated in Refs. [67][68][69] and it is suggested that higher precision experimental data are needed. Indeed, there is no evidence for the three P c resonances in the measurement of the γp → J=ψp cross section by the GlueX experiment [70] with not enough statistics, where the molecular model cannot be ruled out with the upper limits of the branching fractions of P c → J=ψp.…”
Section: Introductionmentioning
confidence: 99%
“…To explain these P c states, various theoretical interpretations were proposed, such as loosely-bound meson-baryon molecular states [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and tightly-bound pentaquark states [39][40][41][42][43][44][45][46][47][48], etc. Since they have only been observed in the J/ψ p invariant mass spectrum by LHCb [3,4], it is crucial to search for some other decay channels in order to better understand their nature.…”
Section: Introductionmentioning
confidence: 99%